Isolation and characterization of a novel lytic bacteriophage Pv27 with biocontrol potential against Vibrio parahaemolyticus infections in shrimp - Hien,Vu Thi; Lanh,Pham Thi; Pham,Thao Thi Phuong; Tran,Khang Nam; Duy,Nguyen Dinh; Hoa,Nguyen Thi; Canh,Nguyen Xuan; Nguyen,Quang Huy; Kim,Seil; Quyen,Dong Van (PeerJ, 2025)
Background Vibrio parahaemolyticus is a major disease-causing species of Vibrio that is pathogenic to both farmed shrimp and humans. With the increasing spread of antibiotic-resistant V. parahaemolyticus strains, bacteriophages (or phages) are considered potential agents for biocontrol as an alternative to antibiotics. In this study, a bacteriophage capable of lysing V. parahaemolyticus, named Pv27, was isolated, characterized, and evaluated for its potential to control Vibrio infections as a natural therapy. Methods Phage Pv27 was isolated using the double-layer agar technique and its morphology was characterized by transmission electron microscopy (TEM). We further assessed the host range specificity, optimal multiplicity of infection (MOI), one-step growth kinetics, and environmental stability of Pv27 under various pH and temperature conditions. The inhibitory activity of Pv27 against V. parahaemolyticus was evaluated in vitro. Finally, genomic analysis of Pv27 was conducted through whole-genome sequencing, followed by functional annotation of open reading frames (ORFs) and phylogenetic analysis. Results Phage Pv27 exhibited a Myovirus-like morphology, characterized by an icosahedral head (92.7 ± 2 nm) and a contractile tail (103 ± 11 nm), and belongs to the class Caudoviricetes. Pv27 demonstrated high lytic activity against its host cells, with a short latent period of approximately 25 minutes and a large burst size of 112 plaque-forming units (PFU) per infected cell. The phage displayed significant tolerance to a wide pH range (from 3 to 11) and remained heat-stable at temperatures up to 60 °C for 90 min. Genetically, Pv27 possesses a circular double-stranded DNA genome spanning 191,395 base pairs, with a G + C content of 35% and comprising 355 open reading frames (ORFs). Remarkably, up to 23 tRNA genes were identified in its genome, while no genes associated with antibiotic resistance, virulence, or lysogeny were detected, suggesting its potential as a valuable biocontrol agent. Results from the VIRIDIC, Basic Local Alignment Search Tool (BLAST) and phylogenetic analyses revealed that Pv27 is closely related to the two known Vibrio phages, phiKT1024 and phiTY18. Several genes associated with enhanced environmental competitiveness were also identified in the Pv27 genome, including those encoding a PhoH-like phosphate starvation-inducible protein and endolysin. Phage Pv27 effectively lyses V. parahaemolyticus highlighting its potential as a biocontrol agent.
Keywords: Vibrio parahaemolyticus; Shrimp; Bacteriophages; Biocontrol; Transmission electron microscopy (TEM); Host range; Aquaculture; Acute hepatopancreatic necrosis disease (AHPND); Phage therapy